Aivilik Inuit woman (""Jumbo"") with tattoos, Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1904)
A young Inuit woman identified as ""Jumbo,"" a member of the Iwillic [sic] group, poses in traditional dress in front of a white back-cloth, Hudson Bay, February 16, 1904. Tattoos are visible on her face. Infrastructure Lifestyle Title supplied by cataloger. Information from original envelope identifies this as Photo 15, # 30. The number 31 is etched into the emulsion on the plate. ""Iwillic"" refers to the Aivilik or Aivillingmiut, a group of Iglulik Inuit. These Inuit of the west coast region of Hudson Bay were closely associated with Captain George Comer and the American whalers for many years. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. This is one of a group of photos taken by Comer to record facial tattooing of various Inuit groups of Hudson Bay. He had Aivilik women paint their faces to simulate the tattooing styles of various other groups, in this case, a group he identifies as the ""Southampton Natives.""